The Detection of Surfactant Proteins A, B, C and D in the Human Brain and Their Regulation in Cerebral Infarction, Autoimmune Conditions and Infections of the CNS - Schob, Stefan; Schicht, Martin; Sel, Saadettin; Stiller, Dankwart; Kekule, Alexander; Paulsen, Friedrich; Maronde, Erik; Bräuer, Lars (PLoS ONE, 2013)
Surfactant proteins (SP) have been studied intensively in the respiratory system. Surfactant protein A and surfactant protein D are proteins belonging to the family of collectins each playing a major role in the innate immune system. The ability of surfactant protein A and surfactant protein D to bind various pathogens and facilitate their elimination has been described in a vast number of studies. Surfactant proteins are very important in modulating the host's inflammatory response and participate in the clearance of apoptotic cells. Surfactant protein B and surfactant protein C are proteins responsible for lowering the surface tension in the lungs. The aim of this study was an investigation of expression of surfactant proteins in the central nervous system to assess their specific distribution patterns. The second aim was to quantify surfactant proteins in cerebrospinal fluid of healthy subjects compared to patients suffering from different neuropathologies. The expression of mRNA for the surfactant proteins was analyzed with RT-PCR done with samples from different parts of the human brain. The production of the surfactant proteins in the brain was verified using immunohistochemistry and Western blot. The concentrations of the surfactant proteins in cerebrospinal fluid from healthy subjects and patients suffering from neuropathologic conditions were quantified using ELISA. Our results revealed that surfactant proteins are present in the central nervous system and that the concentrations of one or more surfactant proteins in healthy subjects differed significantly from those of patients affected by central autoimmune processes, CNS infections or cerebral infarction. Based on the localization of the surfactant proteins in the brain, their different levels in normal versus pathologic samples of cerebrospinal fluid and their well-known functions in the lungs, it appears that the surfactant proteins may play roles in host defense of the brain, facilitation of cerebrospinal fluid secretion and maintenance of the latter's rheological properties. © 2013 Schob et al.
CRIS-Team Scopus Importer:2022-08-05